Perancangan Ulang Tata Letak Laboratorium Produksi Menggunakan Metode Systematic Layout Planning dan Blocplan - Pramono, Ashar; Husda, Baso Riadi; Anwar, Fahri; Romadin, Achmad; Erniyani (JATI UNIK : Jurnal Ilmiah Teknik dan Manajemen Industri, 2025)
The current layout of the production laboratory still faces obstacles that hinder both practicum activities and production processes. Inefficient machine placement causes long material transfer distances, while simultaneous machine usage leads to activity congestion that disrupts workflow. This study aims to redesign the laboratory layout by applying Systematic Layout Planning (SLP) in the higher education context. Data were collected through purposive sampling, covering existing conditions, material flow, and space requirements. The analysis was carried out using SLP to generate alternative layouts, which were then evaluated with the Blocplan program as an optimization tool. The results show that the initial layout produced material transfer distances of 125 m in the Welding Lab, 50 m in the Milling Lab, and 88 m in the Turning Lab. The proposed SLP layout reduced these distances to 55 m, 30 m, and 62 m, while Blocplan only achieved 75 m, 43 m, and 73 m, respectively. Thus, SLP proved more effective than Blocplan, reducing transfer distances by more than 50% in several laboratories. This study contributes theoretically by enriching the literature on laboratory layout and practically by offering a more efficient design that can serve as a reference for developing practicum facilities in higher education.